Cytotoxic Activity of Flavonols from Macaranga gigantea (Rchb.f. & Zoll.) Müll.Arg. - Rino Wanandri Salam Rewa; Ratih Dewi Saputri; Tjitjik Srie Tjahjandarie; Mulyadi Tanjung (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2020)
Two flavonols, glyasperin A (1), and meliternatin (2) has been isolated from the leaves of Macaranga gigantea (Rchb.f. & Zoll.) Müll.Arg. Extraction and isolation of flavonols were used methanol with the maceration method. The process of fractionation and purification used column chromatography and radial chromatography. The structure of both flavonols was determined by spectroscopic methods, including UV-Vis, IR, HRESIMS, 1D NMR (1H, and 13C-NMR) and 2D NMR (HMBC and HMQC). The cytotoxic activity of glyasperin A (1), and meliternatin (2) toward P-388 leukemia murine cells by MTT method, showing IC50 values 3.44 and 30.04 µg/mL, respectively.